Revitalisasi Sarana Penunjang Pantai Seger Kuta Melalui Pembuatan Papan Petunjuk Jalan - Ingga Jaya Sampurna; Nuranjani Nuranjani; Lalu Gede Agung; Heri Setiawan; Baiq Niswatul Khair (Educational Consultant & Counseling Career (EC3) Mataram, 2024)
This service aims to support the development of Seger, Kuta, Mandalika beach tourist destinations. The method used in the activity of making road signs at Seger Beach begins with a location survey, designing a simple but informative sign design, as well as making and installing sign boards at a predetermined location. The activity was carried out on Wednesday 20 October 2021. The activity involved the KKN team and the community around Seger Beach, Kuta. The activity was carried out well and all road signage was installed. The hope of the Mataram University KKN team is that this road sign will be useful for visitors who are going to Seger Beach.